INFLUENCE OF CONCRETE-PICTORIAL-ABSTRACT (CPA) APPROACH TOWARDS THE ENHANCEMENT OF MATHEMATICAL CONNECTION ABILITY OF ELEMENTARY SCHOOL STUDENTS - Putri, Hafiziani Eka; Misnarti, Misnarti; Saptini, Ria Dewi (Universitas Pendidikan Indonesia, 2018)
Abstract:. The study aims to examine the influence of CPA learning approach towards the enhancement of mathematical connection ability of elementary school students. The present research is a quasi experiment using pretest and posttest design controls in Mathematics applied to 39 elementary school students in Purwakarta, West Java, Indonesia. The results of the study show that mathematical connection ability of elementary school students who were taught using CPA learning approach is enhanced than the elementary school students who were taught using conventional learning as a whole group of high and low achiever students according to their mathematical prior ability.Â Abstrak: Penelitian ini bertujuan untuk menguji pengaruh pendekatan pembelajaran CPA terhadap peningkatan kemampuan koneksi matematika siswa sekolah dasar. Penelitian ini adalah kuasi eksperimen dengan menggunakan kontrol desain pretest dan posttest dalam Matematika diterapkan kepada 39 siswa sekolah dasar di Purwakarta, Jawa Barat, Indonesia. Hasil penelitian menunjukkan bahwa kemampuan koneksi matematika siswa sekolah dasar yang diajarkan menggunakan pendekatan pembelajaran CPA lebih meningkat daripada siswa sekolah dasar yang diajar menggunakan pembelajaran konvensional secara keseluruhan dalam kelompok siswa berprestasi tinggi dan rendah sesuai dengan kemampuan matematika mereka sebelumnya.